Downregulated TICAM1 is a prognostic biomarker and associated with immune tolerance of Wilms tumor patients - Zhiyi Lu; Fengyin Sun (BMC, 2022)
Abstract Background TIR domain containing adaptor molecule 1 (TICAM1) is a coding gene participating in immune and inflammation responses to malignant cells. However, the role of TICAM1 in Wilms tumor (WT) is rarely known. Materials and methods The expression level of TICAM1 was calculated in the WT TARGET cohort and validated using the GSE66405 cohort. The Kaplan-Meier method was employed to investigate the potential clinical value of TICAM1 and the association between its expression level and clinical features. The influence of TICAM1 on immune infiltration was examined by ESTIMATE, CIBERSORT and MCPcounter algorithms. IC50 of chemotherapeutic drugs was calculated by "pRRophetic" R package. Results TICAM1 was downregulated in WT patients with worse prognosis and a more advanced clinical stage. Moreover, a low expression level of TICAM1 contributed to less immune cell infiltration, few protective immune cells and more antitumor immune cells. Conclusions TICAM1 exerts a significant impact on the prognosis, progression and immune infiltration condition of WT.